Diagnostic value of QRS and S wave variation in patients with suspicion of acute pulmonary embolism - Çağdaş, Metin; Karakoyun, Süleyman; Rencüzoğulları, İbrahim; Karabağ, Yavuz; Artaç, İnanç; İliş, Doğan; Hamideyin, Şerif; Karayol, Sibel; Çiftçi, Handan; Çınar, Tufan (The American journal of emergency medicine, 2018)
This study aimed to investigate the diagnostic value of QRS and S wave variation in patients admitted to the emergency department with suspicion of acute pulmonary embolism (APE). Computerized tomographic pulmonary angiography (CTPA) was performed in 118 consecutive patients to evaluate patients with suspected APE, and 106 subjects with appropriate electrocardiogram and CT images constituted the study population. Using CTPA, APE was diagnosed in 48.1% (n:51) of the study population. The comparison of patients with APE and those without APE revealed that increased heart rate, right axis deviation of QRS axis, complete or incomplete right bundle branch block, prominent S wave in lead D1, increased QRS duration, percentage of QRS (9,8[4,8–19,0] vs 3,8[2,7–71]; p<0,001), S wave variation (22,3[9,6–31,9] vs 4,8 [2-8]; p<0,001) and ΔS wave amplitude (1.1[0.5–1.5] vs 0.2[0.1–0.5]; p<0.001) were significantly associated with APE, but no relationship was detected with respect to the presence of atrial arrhythmias, clockwise rotation of the horizontal axis, fragmentation, ST segment deviation, T wave inversion, and S1Q3T3 and S1S2S3 patterns. The percentage of S wave variation (OR: 1072 per 1% increase, 95% CI:1011–1137) was found to be an independent predictor of APE. ΔS wave amplitude>0.5mm predicted APE with a sensitivity of 72.6% and a specificity of 74.6% (AUC:0.805, 95% CI: 0.717–0.876; p<0.001). The present study demonstrated that QRS and S wave variation could be useful electrocardiographic signs for the diagnosis of APE.